Social networking amid social differentiation in the adoption of improved technologies: A case study in Rajasthan, India - Varshney, Deepak; Joshi, Pramod Kumar; Roy, Devesh (International Food Policy Research Institute, 2019)
This paper evaluates the role of social networks in the adoption of mustard hybrids. The objectives of the paper are (i) to examine how the farmer’s adoption decision relates to the adoption choices of their network members particularly in case of hybrids; (ii) to test whether the lower-caste (Scheduled Caste/Scheduled Tribe [SC/ST]) farmers relied more on social networks for information as compared to the higher-caste (non-SC/ST) farmers; and (iii) to explore whether social network effects are more pronounced when farmers interact within their caste as compared to outside the caste, the issue of homophily versus heterophily. The paper follows the model of social learning in Bandiera and Rasul (2006) extended by introducing the individual level covariates of network members. Further, we try to address endogeneity concerns by including village fixed effects and by analyzing the social network effects in a dynamic adoption framework. We establish evidence of endogenous effects in the adoption choices of hybrids i.e. more pronounced for the lower caste (schedule caste/tribe) vis-a-vis the higher caste. Further, network effects are stronger with homophily within the same caste.